2018
DOI: 10.1108/jhom-08-2018-0219
|View full text |Cite
|
Sign up to set email alerts
|

Costs will rather increase

Abstract: Purpose The purpose of this paper was to study the unfolding of an urgent and extensive decommissioning program in Sweden, focusing on the public’s reactions and their arguments when opposing the decommissioning activities. Design/methodology/approach The public’s responses were studied through local media. Its content was surveyed and divided into actions and arguments. The arguments were further analyzed and categorized into inductively developed themes. Findings Protest activities, such as demonstration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In 2020, a national evaluation reported that Region Dalarna had the lowest healthcare cost per inhabitant among Sweden’s 21 regions (KOLADA, 2020). Furthermore, there was, unexpectedly, little resistance from the clinics and clinic managers involved in the decommissioning activities in relation to the many and extensive changes they had made (KPMG, 2016; KPMG, 2018; Fredriksson and Moberg, 2018). A national evaluation indicated a positive trend in quality of care for the primary care, surgery, and medicine divisions during the decommissioning processes, as well as in indicators of patient safety (Yang and Buijs, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In 2020, a national evaluation reported that Region Dalarna had the lowest healthcare cost per inhabitant among Sweden’s 21 regions (KOLADA, 2020). Furthermore, there was, unexpectedly, little resistance from the clinics and clinic managers involved in the decommissioning activities in relation to the many and extensive changes they had made (KPMG, 2016; KPMG, 2018; Fredriksson and Moberg, 2018). A national evaluation indicated a positive trend in quality of care for the primary care, surgery, and medicine divisions during the decommissioning processes, as well as in indicators of patient safety (Yang and Buijs, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…This fact may have influenced them to think of the decommissioning programme as successful in terms of balancing the economy. 27 , 28 Hence, longitudinal studies may be appropriate to further study the sustainability of this type of programmes and we suggest this approach for future studies. Lastly, because we exclusively interviewed CMs, who may naturally focus on events closely related to the clinic, this could have led to an underestimation of factors of importance situated further away, for example, at the political level or the role of interest groups.…”
Section: The Most Important Influences: Early Involvement and Adaptiv...mentioning
confidence: 99%
“…One such potential driver in this case may be that, at the time of the interview, the clinic managers were aware that the region's economy had improved considerably. This fact may have influenced them to think of the decommissioning programme as successful in terms of balancing the economy (29,30). This change required reformulation of the programme, which was performed by the CMs rather than the region leadership.…”
Section: The Sustainability Of the Programmementioning
confidence: 99%